2009
DOI: 10.1177/0042098008099356
|View full text |Cite
|
Sign up to set email alerts
|

`Ageing in Place'? Exploring Elderly People's Housing Preferences in Spain

Abstract: The greater visibility of societal ageing and higher share of individuals with disabilities have created new challenges for housing and urban policies. Housing needs can influence individual choice of living environment and the willingness to undertake housing improvements. This is especially relevant in southern European countries where the family is still the main provider of care for the elderly. This study makes an empirical analysis of the underlying preferences for housing and perceptions of housing suit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(114 citation statements)
references
References 41 publications
7
99
0
8
Order By: Relevance
“…A third change is that multigenerational households have declined in industrialized countries. This is due to both rising incomes, which enable generations to live separately, and an increasing proportion of people living some distance from their parents (4,15,16,31,42).…”
Section: Individual or Social Responsibility-shift Toward Shared Respmentioning
confidence: 99%
“…A third change is that multigenerational households have declined in industrialized countries. This is due to both rising incomes, which enable generations to live separately, and an increasing proportion of people living some distance from their parents (4,15,16,31,42).…”
Section: Individual or Social Responsibility-shift Toward Shared Respmentioning
confidence: 99%
“…The meaning of home is not the same throughout the life course� each life stage involves a specific housing demand and implies a particular need of living conditions (oswald and wahl, 2005)� Specifically during old age, the influence of the residential context on the wellbeing is higher than during other life stages such as early adulthood� The reason for that is, firstly, that older adults stay at home more compared with the rest of the population (Butler, 1986)� due to the decline of physical functions or changes in their routines after retirement, they tend to reduce their social networks and daily habits to the domestic sphere� These transformations can unleash negative effects on older people's wellbeing in a psychological and physical sense, such as isolation, dependence on relatives or loneliness (Boyce et al�, 2003(Boyce et al�, )� as evans et al� (2002 have shown, housing quality has a positive effect on the perceived wealth and life satisfaction of older adults� at the same time, the residential dynamics are shaped not only by individual needs, but also by household or family needs (dykstra and van wissen, 1999)� The relocation choices of older individuals are closely linked with their kinship living decisions� Because of that, it is necessary to consider the ties established between family members as a determinant factor in the mobility paths, both to provide or to limit the movement� Secondly, the importance of housing at older ages lies in the emotional attachment that older people have to their homes� This emotional attachment arises from the fact that most important life events take place in the domestic sphere, especially in the family dimension, such as the birth and bringing up of children (Clapham, 2005)� The preference of the vast majority of older adults is to remain in their own private dwelling until some disability or chronic disease forces them to move to an institution (Costa-Font, 2009)� also in a psychological sense, at old ages the dwelling symbolises independence and autonomy which determine older people's wellbeing (gurney and Means, 1997)� nevertheless, the emotional attachment that older people have to their homes can lead to an imbalance between the residential needs and the real conditions of the dwelling they reside (Cortés and laínez, 1998)� This imbalance results from many older adults living in dwellings acquired in previous life stages, when their needs were different� The mismatch between housing conditions and residential needs at older ages occurs in three different ways; a mismatch in the dwelling (lack of bathroom or shower, shortage of space, number of rooms), a mismatch in the building (no elevator or stairs, age of the building, number of dwellings, access), and a mismatch in the neighbourhood (noise, pollution, parks in the area) (Cortés and laínez, 1998)� in consequence, a dissatisfactory housing context can affect the wellbeing of older people, increasing their vulnerability and causing a worsening of their life quality� regarding the macro level factors that encourage older adults to remain at home, public policies in europe, with different implementation degrees depending on the country, have been structured to benefit 'ageing in place'� 'ageing in place' consists of different socio-economic measures addressed to support older people at home until it is absolutely necessary for them to move� at this point, the 'ageing in place' is the widely promoted residential way of ageing in western societies� Based on this, some authors have suggested new hypotheses about the residential behaviours of elderly europeans� on the one hand, some consider that mob...…”
Section: Home and Wellbeing Linkage During Old Agementioning
confidence: 99%
“…Concomitant with the relocation approach, the research regarding ageing in place underlined the psychological reasons to remain in the same home and neighbourhood: the sense of attachment, identity and environmental familiarity [15,16], better physical health, improved mental wellbeing, and a high quality of life [17]. Indeed, the vast majority of older homeowners prefer to "ageing in place", defined as the ability to live in one's own home and community safely, independently and comfortably, regardless of age, income, or ability [18][19][20]. Nevertheless, ageing in place is a concept that matches the needs of older adults to the policies of various governments.…”
Section: Introductionmentioning
confidence: 99%